Pengaruh Pembelajaran PAI Dan PKN Terhadap Penguatan Karakter Profil Pelajar Pancasila Pada Peserta Didik - Afifah, Auliya (Universitas Wahid Hasyim Semarang, 2023)
Our young generation is currently experiencing moral degradation, therefore proper handling is needed, one of which is through strengthening the character of the Pancasila student profile which is applied in every learning activity.This study aims to determine the effect of PAI and Civics learning on strengthening the profile of Pancasila students. The type of research used is quantitative. The approach used in this research is descriptive. This research was conducted at SDN 01 Sawah Besar, Gayamsari District, Semarang City. The population in this study were all students of SDN 01 Sawah Besar. The researchers took samples in grade 5, which consisted of 24 students. Data collection techniques in this study used observation, interviews, documentation, and questionnaires. There are 3 variables in this study which include: The Effect of PAI Learning (X1), The Effect of Citizenship Education Learning (X2), and Strengthening the Character Profile of Pancasila Students (Y1). The results of this study are that there is an influence given by PAI Learning and Civics Learning by 0.398 or 39.8% on Strengthening the Characteristics of Pancasila Student Profiles (Y) of students, while 60.2% is influenced by other aspects. Based on the value of Fcount = 6.946 and Ftable = 5.780. So, Fcount > Ftable, 6.946 > 5.780 which means that there is a significant influence between PAI and Civics Learning on Strengthening the Characteristics of Pancasila Student Profiles.